PRINSIP DASAR PENGGUNAAN AKAD DALAM PENERBITAN SURAT BERHARGA SYARIAH NEGARA DI INDONESIA - Burhanuddin Susamto (Fakultas Syariah (Syari'ah Faculty ), 2019)
This article is aimed to offer the basic principles of using the contracts in issuing of SBSN derived from the analysis result toward the muamalah contracts and the fatwa DSN-MUI. The position of the fatwa DSN-MUI in issuing SBSN of Indonesia is binding because it has been legitimized by the laws. Therefore, in every issuing SBSN, a fatwa is always requested to obtain a statement of conformity with sharia principles regarding the structure of the contract used. The enactment of contracts in issuing SBSN adjusts to the needs of the government. If the government want to procure state-owned goods, both ready stock and orders, then the scheme will be used is purchase contract. If the government needs to get the benefits of goods, the contract scheme used is lease. If the government needs capital to finance productive projects, the contract scheme used is profit/ loss sharing. SBSN certificates that have been issued according to those contracts scheme then are distributed to investors by using purchase contract.